Management of Diabetic Foot Ulcers on Adjunctive Therapy: A Systematic Review - Zulfikar Peluw; La Rakhmat Wabula (Humanistic Network for Science and Technology (HNST), 2019)
Diabetic foot ulcers is a common complication of Diabetes Mellitus and was became world health global issue. The adjunctive therapy has become the latest modality in recent years, but there were not much significant research to support its utilization as a diabetic foot ulcer treatment standard. This review aims to assess the effectiveness of various adjunctive therapies for diabetic foot ulcers. Using electronic databases, such as Scopus, PubMed, Embase, Ovid Technologies, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane, and Web of Science databases were systematically searched in June 2013 for systematic reviews published after 2004 and randomized controlled trials (RCTs) published in 2012–2013. Many therapeutic modalities are available to treat DFU. Quality high-level evidence exists for standard care such as off-loading. Evidence for adjunctive therapies such as negative pressure wound therapy, skin substitutes, and platelet-derived growth factor can help guide adjunctive care but limitations exist in terms of evidence quality. Given the diversity of therapies, future studies must deﬁne the populations that most beneﬁt from each therapy by utilizing clear and strict inclusion and exclusion criteria. Keywords: Adjunctive therapy, Diabetic foot ulcers